Quantification of within patient Staphylococcus aureus phenotypic heterogeneity as a proxy for presence of persisters across clinical presentations - Baer, Julian (University of Dundee, 2022)
Staphylococcus aureus was isolated from patients suffering cardiovascular, prosthetic joint or other infections and plated on Columbia sheep blood agar. Macroscopic time-lapse imaging was performed to quantify colony appearance-time and growth-rate. As a baseline reference, the same time-lapse imaging protocol was used after subculturing clinical isolates in tryptic soy broth until bacteria reached exponential growth phase.
Experiment Description
Bacteria were directly isolated from patient material and then spread-plated on Columbia Sheep Blood agar plates. Samples were endpoint (single isolated timepoint, usually 24h and 48h) imaged.
Keywords: FOS: Biological sciences; FOS: Biological sciences